Overall Neutrophil-to-Lymphocyte Ratio and SUVmax of Nodal Metastases Predict Outcome in Head and Neck Cancer Before Chemoradiation - Werner, Jonas; Strobel, Klaus; Lehnick, Dirk; Rajan, Gunesh P. (Frontiers in Oncology, 2021)
Introduction This study investigates the pretherapeutic neutrophil-to-lymphocyte ratio (NLR) with markers of tumor metabolism in 18-fluorodeoxyglucose positron emission tomography/computed tomography (FDG-PET/CT) and their potential prognostic value in head and neck cancer patients prior to primary chemoradiation. Materials and Methods NLR and metabolic markers of primary tumor and nodal metastases including maximum standardized uptake value (SUVmax), metabolic tumor volume (MTV), and total lesion glycolysis (TLG) were retrospectively assessed in a consecutive cohort of head and neck squamous cell cancer patients undergoing primary chemoradiation. The main outcome measure was survival. Results The study included 90 patients of which 74 had lymph node metastases at diagnosis. Median follow-up time of nodal positive patients (n=74) was 26.5 months (IQR 18–44). The NLR correlated significantly with metabolic markers of the primary tumor (TLG: rs=0.47, P<0.001; MTV: rs=0.40, P<0.001; SUVmax: rs=0.34, P=0.003), but much less with FDG-PET/CT surrogate markers of metabolic activity in nodal metastases (TLG: rs=0.15, P=0.19; MTV: rs=0.25, P=0.034; SUVmax: rs=0.06, P=0.63). For nodal positive cancer patients, multivariate analysis showed that an increased NLR (HR=1.19, 95% CI=1.04-1.37, P=0.012) and SUVmax of lymph node metastasis (HR=1.09; 95% CI=0.99-1.19; P=0.081) are independently predictive of disease-specific survival. High NLR had a negative prognostic value for overall survival (HR=1.16, 95% CI=1.02-1.33, P=0.021). Conclusion NLR correlates positively with metabolic markers of the primary tumor, suggestive of an unspecific inflammatory response in the host as a possible reflection of increased metabolism of the primary tumor. SUVmax of lymph node metastases and the NLR, however, show no correlation and are independently predictive of disease-specific survival. Therefore, their addition could be used to improve survival prediction in nodal positive head and neck cancer patients undergoing primary chemoradiation.